(untitled) (Bangladesh Journal of Plastic Surgery, 2011)
Background of the study: Aplasia cutis congenita refers to a heterogenous group of disorders in which localized areas of skin are absent or scarred at birth. No definite etiology is available in literature. Strong genetic predisposition is suspected. Objectives: To overview observed cases and study the rare congenital anomaly. Methods: Total 4 cases that reported in the department of plastic surgery, Dhaka Medical College Hospital included in the study. All the necessary data plotted and analyzed for purpose. Results: None of the patients had positive family history. No parents had history of consanguinity of marriage. None of them had history teratogen exposure or taking drug during pregnancy. No positive history of maternal smoking or alcohol consumption noted. Both legs were most frequently involved 3 cases. Followed by scalp and hand. All the patients were advised for regular follow up. 1 patient died at the age of 30 days in home and lost follow up. Other patients improved after regular dressings DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8801 BDJPS 2010; 1(2): 20-22